Behaviour of fibre reinforced cemented sand at high pressures - -, Salah-ud-din (2012)
Several well established techniques of soil stabilisation and soil reinforcement are available to improve properties of geotechnical materials. However, the addition of fibre into soils has its unique potential as a reinforcing agent. This is because a friction between fibre and soil particles increases the bonding between the particles of soils and this can improve the plasticity, stress-strain behaviour and failure characteristics of both cemented and uncemented soils. It also reduces the brittleness of the cemented sand. Numerous experiments on fibre-reinforced granular materials have been carried out by several researchers. However, the behaviour of fibre-reinforced cemented granular soils has not been fully understood yet. Furthermore, most experimental studies of fibre reinforced cemented materials have been carried out at relatively low confining pressures. As a result, more experiments are still needed to understand complicated behaviour of soil-cement-fibre composite materials. The main objective of this thesis is to analyse the behaviour of fibre reinforced cemented sand under wide range of confining pressures.